Breakfast Frequency and Diabetes Incidence in a Cohort of Middle-Age Women. (7th June 2021) - Martinez, Claudia; Ortíz-Panozo, Eduardo; Stern, Dalia; Cortés, Adrián; Mattei, Josiemer; Campos, Hania; Flores-Aldana, Mario; Lajous, Martín
Abstract: Objectives: To examine the relation between breakfast frequency and incidence of diabetes in middle-aged women. Methods: The Mexican Teacher´s Cohort is a prospective study in women. We included 71, 373 participants at baseline (2006–2008). Participants were classified according to breakfast frequency 0, 1–3, 4–6, or 7 d/wk; and meal frequency 1–2, 3–4, or ≥5 meals/d. Diabetes was self-reported. We used Cox proportional hazards models to calculate hazard ratios (HR) and 95% confidence intervals (CI) to estimate the association between breakfast frequency and diabetes incidence. Models were adjusted for sociodemographic and lifestyle confounders that are associated with breakfast consumption and are risk factors for diabetes. Stratified analyses were performed for age, birth weight, indigenous background, and physical activity. Results: We identified 3, 613 new diabetes cases during a median of 2.2 years of follow-up. Prevalence of daily breakfast consumers was 25%. After adjustment for known risk factors for diabetes, compared to 0 d/wk, women who eat daily breakfast had 12% lower rate of diabetes (HR = 0.88; 95% CI 0.78, 0.99; p-trend = 0.0018). One day additional per week having breakfast decreased the risk of diabetes (HR = 0.98; CI 0.97, 0.99). In stratified analysis, women with indigenous background who consumed breakfast 4–6 d/wk and 7 d/wk vs. 0 d/wk shown lower risk (HR = 0.68; 95% CI 0.47, 0.98) and HR = 0.76; 95% CI 0.76 (0.51, 1.15) respectively; p-interaction = 0.197). Conclusions: Daily breakfast was associated with a lower incidence of diabetes, independently of dietary and lifestyle factors. Likely effect modifiers as ethnicity warrants more research. Daily breakfast consumption is a potential component of diabetes prevention. Funding Sources: This work is supported by the American Institute for Cancer Research (05B047) and Consejo Nacional de Ciencia y Tecnología (CONACyT) grant S0008-2009-1: 000000000115312.